Atmospheric carbon monoxide and hospitalization for mental and behavioral disorders: insights from a longitudinal study in Shijiazhuang - Peihua Hu; Wenting Lu; Xian Gao; Yating Li; Yanli Yang; Wanyi Yin; Liang Dong; Ruojia Ren; Xueyi Wang (Frontiers in Psychology)
Background and aimCarbon monoxide (CO), a prevalent environmental pollutant, has been implicated in adverse mental health outcomes, but the mechanistic relationship between atmospheric CO levels and hospital admissions for mental and behavioral disorders remains unclear. This study investigates the epidemiological link between atmospheric CO and hospitalizations for mental health conditions in Shijiazhuang, China.MethodologyClinical data from patients hospitalized with mental and behavioral disorders at The First Hospital of Hebei Medical University between January 2014 and December 2020 were analyzed. Daily atmospheric CO levels, temperature, and relative humidity were concurrently monitored. A generalized additive model (GAM) was used to explore the correlation between CO levels and hospital admissions. Blood samples from patients with depressive disorders were analyzed for MAPK3 expression, and a mouse model of CO-induced depression was employed to further explore the molecular mechanisms.ResultsA total of 15,890 hospitalization records were included. A significant positive correlation was identified between CO levels and the number of daily hospitalizations, with the strongest effects observed when CO concentrations exceeded 40 μg/m3. This association was most pronounced in males and individuals aged over 45, as well as during both warm and cold seasons. A two-pollutant model confirmed CO as a major factor affecting hospitalizations, independent of other pollutants like nitric oxide and sulfur dioxide. Additionally, elevated MAPK3 expression was found in the blood samples of depressed patients, and treatment with the MAPK inhibitor PD98059 alleviated CO-induced depression in a mouse model.ConclusionThis study provides compelling evidence for a significant association between atmospheric CO and hospitalizations for mental and behavioral disorders. The findings suggest that CO exposure may exacerbate mental health conditions, particularly in vulnerable populations. These insights underline the importance of air quality management and highlight potential pathways for therapeutic interventions targeting CO-induced mental health disorders.